Loss of Cardiac Ferritin H Facilitates Cardiomyopathy via Slc7a11-Mediated Ferroptosis. Issue 4 (31st July 2020) - Fang, Xuexian; Cai, Zhaoxian; Wang, Hao; Han, Dan; Cheng, Qi; Zhang, Pan; Gao, Feng; Yu, Yingying; Song, Zijun; Wu, Qian; An, Peng; Huang, Sicong; et al.
Abstract : Rationale: Maintaining iron homeostasis is essential for proper cardiac function. Both iron deficiency and iron overload are associated with cardiomyopathy and heart failure via complex mechanisms. Although ferritin plays a central role in iron metabolism by storing excess cellular iron, the molecular function of ferritin in cardiomyocytes remains unknown. Objective: To characterize the functional role of Fth (ferritin H) in mediating cardiac iron homeostasis and heart disease. Methods and Results: Mice expressing a conditional Fth knockout allele were crossed with 2 distinct Cre recombinase-expressing mouse lines, resulting in offspring that lack Fth expression specifically in myocytes (MCK-Cre) or cardiomyocytes (Myh6-Cre). Mice lacking Fth in cardiomyocytes had decreased cardiac iron levels and increased oxidative stress, resulting in mild cardiac injury upon aging. However, feeding these mice a high-iron diet caused severe cardiac injury and hypertrophic cardiomyopathy, with molecular features typical of ferroptosis, including reduced glutathione (GSH) levels and increased lipid peroxidation. Ferrostatin-1, a specific inhibitor of ferroptosis, rescued this phenotype, supporting the notion that ferroptosis plays a pathophysiological role in the heart. Finally, we found that Fth-deficient cardiomyocytes have reduced expression of the ferroptosis regulator Slc7a11, and overexpressing Slc7a11 selectively in cardiomyocytes increased GSH levels and prevented cardiac ferroptosis. Conclusions: Our findings provide compelling evidence that ferritin plays a major role in protecting against cardiac ferroptosis and subsequent heart failure, thereby providing a possible new therapeutic target for patients at risk of developing cardiomyopathy. Abstract : Supplemental Digital Content is available in the text.